Ofatumumab Versus Rituximab Salvage Chemoimmunotherapy in Relapsed or Refractory Diffuse Large B-Cell Lymphoma: The ORCHARRD Study - van Imhoff, Gustaaf W.; McMillan, Andrew; Matasar, Matthew J.; Radford, John; Ardeshna, Kirit M.; Kuliczkowski, Kazimierz; Kim, WonSeog; Hong, Xiaonan; Goerloev, Jette Soenderskov; Davies, Andrew; Barrigón, María Dolores Caballero; Ogura, Michinori; et al. (Journal of clinical oncology, 2017)
Purpose We compared the efficacy of ofatumumab (O) versus rituximab (R) in combination with cisplatin, cytarabine, and dexamethasone (DHAP) salvage treatment, followed by autologous stem-cell transplantation (ASCT) in patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL). Patients and Methods Patients with CD20 DLBCL age ≥ 18 years who had experienced their first relapse or who were refractory to first-line R-CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone)-like treatment were randomly assigned between three cycles of R-DHAP or O-DHAP. Either O 1,000 mg or R 375 mg/m was administered for a total of four infusions (days 1 and 8 of cycle 1; day 1 of cycles 2 and 3 of DHAP). Patients who experienced a response after two cycles of treatment received the third cycle, followed by high-dose therapy and ASCT. Primary end point was progression-free survival (PFS), with failure to achieve a response after cycle 2 included as an event. Results Between March 2010 and December 2013, 447 patients were randomly assigned. Median age was 57 years (range, 18 to 83 years); 17% were age ≥ 65 years; 63% had stage III and IV disease; 71% did not achieve complete response (CR) or experience response for < 1 year on first-line R-CHOP. Response rate for O-DHAP was 38% (CR, 15%) versus 42% (CR, 22%) for R-DHAP. ASCT on protocol was completed by 74 patients (33%) in the O arm and 83 patients (37%) in the R arm. PFS, event-free survival, and overall survival were not significantly different between O-DHAP versus R-DHAP: PFS at 2 years was 24% versus 26% (hazard ratio [HR], 1.12; 95% CI, 0.89 to 1.42; P = .33); event-free survival at 2 years was 16% versus 18% (HR, 1.10; P = .35); and overall survival at 2 years was 41% versus 38% (HR, 0.90; P = .38). Positron emission tomography negativity before ASCT was highly predictive for superior outcome. Conclusion No difference in efficacy was found between O-DHAP and R-DHAP as salvage treatment of relapsed or refractory DLBCL.